Why We Are Not Living in a Computer Simulation - Lim, Abraham (International journal for the study of skepticism, 2022)
Nick Bostrom considered a number of simulations and contended that the probability that we are living in one of them is high or at least nonzero. I present arguments to refute the claim that we are or might be in any one of them.